Alignment of behaviour and tDCS stimulation site induces maximum response: evidence from online tDCS and ERP - Bhattacharjee, Sagarika (2024)
tDCS modulates the activity of the neuronal networks to induce the desired behavioural changes. Two factors determine its effectiveness- (1) whether the network being stimulated is relevant to the task, and (2) if there is a scope for improvement in behavioral performance. To explore this, both dorsal (sub-lexical) and ventral (lexical) reading networks were stimulated (20 min, 2 mA) in 25 healthy young volunteers. Participants performed two reading tasks with different levels of lexical involvement: word fragment completion tasks (WCT) and word association tasks (WAT), while event-related potentials (ERPs) were recorded simultaneously. The study used a within-subject design over three sessions, comparing various electrode montages targeting the dorsal pathway's left inferior parietal lobule or the ventral reading pathway's left middle temporal lobule, as well as sham stimulation. The impact of tDCS sessions (dorsal, ventral, & sham) and task type (WCT & WAT) on priming effects (primed vs. unprimed) of behavioral performance (accuracy and reaction times), and ERP parameters (N400 amplitudes and latencies) were statistically analyzed.It was found that tDCS modulated the performance of WAT only (a task with a lower priming effect). The failure to modulate WCT (larger priming effect) indicated that tDCS was effective for conditions with room for improvement compared to a task where performance has reached the ceiling. Ventral stimulation enhanced accuracy in the WAT condition and shortened the N400 latency of the priming effect. In contrast, dorsal stimulation delayed the priming effect reaction time in the WAT condition and enhanced the N400 amplitude. To conclude, enhancement in performance due to tDCS occurs when the network (ventral) being stimulated aligns with the cognitive demands of the task and there is a scope for improvement.